Gambaran Tingkat Kecemasan Mahasiswa Sarjana Keperawatan Selama Pembelajaran Daring di Universitas ‘Aisyiyah Surakarta - Dini Ika Mawarni; Endah Sri Wahyuni (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
The COVID-19 pandemic has affected various fields globally, not only the health sector but also the education sector. Online learning is learning without meeting in person but virtually through intermediaries. Central Java is a province that occupies the third position with high Covid cases, namely 138,547 (11.7%) of the total cases in Indonesia. The Surakarta region itself occupies the 23rd position out of 35 regions in Central Java, however, the Surakarta Region experienced the highest deflation compared to other regions on the island of Java. The limitations of adaptation to the online learning process during a pandemic have a negative impact, one of which is anxiety. The purpose of this study was to describe the level of anxiety of undergraduate nursing students during online learning at the University of 'Aisyiyah Surakarta. This type of research is descriptive. Sampling technique using stratified random sampling. The sample in the study was 84 respondents. The instrument in this study used an anxiety questionnaireZung Self-Rating Anxiety Scale (SAS). The results showed that the level of anxiety in undergraduate nursing students was in the category of moderate anxiety in as much as 1 respondent (1.2%), mild anxiety in 21 respondents (25%), and no anxiety in 62 respondents (73.8%). From the results of the study, it can be concluded that the majority of respondents are in the age range of 19-20 years, as many as 39 respondents (46.4%), and the majority of respondents are female, as many as 50 respondents (59.5%). The description of the anxiety level of undergraduate nursing students during online learning at the University of 'Aisyiyah Surakarta is a majority in the no anxiety category as many as 62 respondents (73.8%).